Tekanan Normal Hidosefalus Pada Pasien Usia Lanjut: Sebuah Laporan Kasus - Ashira Graciana; Irawaty Hawari (KOLONI, 2026)
Normal pressure hydrocephalus  (NPH) is a potentially reversible cause of gait disturbance, cognitive decline, and urinary incontinence in the elderly population. Diagnosis is often delayed because its clinical manifestations overlap with normal aging and other neurodegenerative disorders, making early recognition crucial for identifying candidates for shunt therapy. We report the case of an 81-year-old woman who presented with chronic dizziness accompanied by a sensation of unsteadiness while walking, a history of recurrent falls, urinary incontinence, and mild cognitive decline. Neurological examination revealed gait disturbance with a positive tandem gait test and a positive sharpened Romberg test. Cognitive assessment showed a Mini Mental State Examination score of 28, with evidence of executive dysfunction on the clock drawing test. Non-contrast cranial CT scan demonstrated ventriculomegaly with cerebral atrophy and extensive degenerative white matter changes, without intracranial hemorrhage. Based on the clinical and radiological findings, the patient was suspected to have idiopathic normal pressure hydrocephalus and was referred for further evaluation and consideration of shunt surgery. The findings in this case are consistent with the typical clinical presentation and pathophysiological features of idiopathic NPH. Recent evidence indicates that shunt procedures, particularly ventriculoperitoneal and lumboperitoneal shunts, can provide meaningful clinical improvement with an acceptable safety profile in carefully selected patients. Early recognition of the characteristic features of NPH and accurate correlation between clinical manifestations and neuroimaging findings are essential for identifying appropriate candidates for shunt therapy and preventing progressive disability in elderly patients.